DESIGN OF HYBRID ENERGY HARVESTING SYSTEM USING SOLAR AND WIND ENERGY ON RANCABUAYA FISHING - Hanifan, Mohamad
Rancabuaya beach in Garut, West Java has a high potential of sun and wind energy. Meanwhile, the Rancabuaya villagers mostly live as fishermen. They need electricity to power the ice box to store the captured fish. This demand for electricity can be fulfilled by the sun and wind energy harvesting. The instruments used to harvest the energy are solar panel and wind turbine. This final project aims to design the instrumentation system of hybrid solar and wind energy harvester that is going to be installed in the fishermen boat. The design consists of electrical and mechanical systems. The energy needed to power the boat for a day is 720 Wh. With daily average wind velocity 4.27 m/s and sun irradiation 672 W/m2, the solar panel can harvest 815 – 817 Wh energy, while the wind turbine can harvest 43 – 62 Wh energy. The electrical design includes the integration of energy harvesting system, the recording and displaying of energy data with data logger, and the monitoring of battery’s ability to store energy. Next, the boat hydrostatic dimension is measured to later determine its stability condition. This mechanical design consists of designing the installation of solar panel and wind turbine, including the dimension and position of their framework. To reach a stable equilibrium condition, the framework of the wind turbine should be installed at a height of 1.7 m. The design that has been made shows that the solar panel and wind turbine chosen can meet the energy required to power the boat. Also, mechanically, the boat will still be stable when installed with energy harvester instruments. It can be concluded that this design of energy harvester system can be applied and installed on the Rancabuaya fishermen boat.